Tuberculosis as a Primary Cause of Oesophageal Stricture: a case report - Mbiine, Ronald; Kabuye, Ronald; Lekuya, Herve Monka; Manyillirah, William (Journal of Cardiothoracic Surgery, 2018)
Tuberculous (TB) oesophagitis is a rare manifestation of dysphagia occurring in 0.3% of all gastro-intestinal tract TB infections as well as 0.15% of all cases of dysphagia and often is misdiagnosed. This report presents a rare manifestation of TB as a cause of oesophageal stricture.
Keywords: Tuberculosis; Oesophageal stricture; Primary cause